Inequality and market concentration - Hotchin, Lachlan,Leigh, Andrew (CESifo, 2024)
Are excessively concentrated markets inequitable as well as inefficient? We explore this issue by analyzing the degree of market concentration in the industries where Australia's wealthiest made their fortunes. Compared with the economy at large, we find that top wealth holders have tended to make their fortunes in industries with a higher-than-average degree of market concentration. Top wealth shares have grown substantially, and from 1990 to 2020, there appears to have been an increase in the propensity of top wealth holders to make their fortunes in highly concentrated industries.
10419/296031
Keywords: Graue Literatur; income distribution; competition; market power